Beak Morphology Variation of Uroteuthis edulis Based on Geometric Morphometrics - Chao WANG; Zhou FANG; Xinjun CHEN (Progress in Fishery Sciences, 2023)
The study of ontogenetic organisms can help us fully understand the law of morphology change and the correlation between the function and morphology of the structure of organisms. To explore the pattern of growth change in U. edulis beak, this study used geometric morphometric methods to analyze the differences in beak size and morphology in different sexes and ontogenetic stages, revealing its ecological implications. Results show some differences in the size of different sexes´ beaks of U. edulis in the ontogenetic process; the beak of female individuals is larger than that of male individuals, but the differences in the beak morphology of different sexes were not significant (P > 0.05). Principal component analysis and a thin-plate spline deformation mesh show that the beak morphology from immature to mature presents different developmental stages; in the ontogenetic process, the hood and wing of the upper and lower beak become larger, the crest protrudes more, the jaw angle gradually becomes smaller, and the rostrum of the upper beak is sharper; however, the rostrum of the lower beak gradually blunted. The multiple regression analysis shows that the morphology change of the upper beak is small in the immature stage, the morphology change is larger in the maturing and mature stages, the pattern of morphology change in the maturing and mature stages is similar, the morphology change of the lower beak is large in the immature and mature stages, the morphology change is small in the mature stage, and the morphology change trend is significantly different in the ontogenetic process. The beak morphology of U. edulis had different growth patterns during different ontogenetic stages. Beaks also showed an allometric growth, possibly related to the feeding and environmental changes during the ontogenetic stage of U. edulis, helping it to grow and develop.